Teachers’ management of cyberbullying on China’s social media sites: A case study in Shandong Province, China - Zhao, Han (Taylor and Francis Ltd., 2022)
In recent years, cyberbullying on social media sites has increased among adolescents and even adults. While there are many factors and forms of cyberbullying, schoolchildren are vulnerable groups that are exposed to cyberbullying threats to their mental and emotional health. On the other hand, teachers have the responsibility in the place of the parent while at school, and they need to manage the issue at bay. This study focuses on the identification and analysis of teachers’ advice about cyberbullying, thus leading to the conceptualization of a decision-making model for the school to guide other teachers on this matter. This study is an explorative case study conducted in a prominent, semi-private international school in Lingyi, Shandong Province, China. With the purposive sampling approach, thirty-two teachers volunteered in this study; to recap and describe their encounters through writing in an online survey form. As analysis, their responses were validated for trustworthiness, while codes are checked through member checking, and eventually thematically analyzed to address the research questions. Findings from this study revealed a list of tactics that were categorized into three themes: (a) Preventive measures; (b) Counter-measures, and (c) Corrective measures. Each of these categories highlights specific ways that teachers suggest their students to when confronted with cyberbullying. Thereafter, each category was integrated as a model of decision-making in cyberbullying for improvements to the standard operating protocol of the researched school. In addition, this study proposes more similar research in other school settings so that more advisory tactics can be accumulated to enable education policymakers, school administrators, and teachers to make better decisions to manage issues associated with cyberbullying. © 2022 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.